Clinico-Demographic Profile of Patients with Acute Coronary Syndrome Presenting to Emergency Department in a Tertiary Care Setting in Nepal - Mishra, Deepak Kumar; Adhikari, Sushil (Journal of National Heart and Lung Society Nepal, 2024)
Background: ACS patients in South Asia present approximately a decade earlier than their counterparts in developed nations due to the high prevalence of modifiable risk factors like hypertension, diabetes, and smoking. This study aimed to find the clinico-demographic profile of ACS patients in a tertiary care hospital in Nepal. Methods: A descriptive cross-sectional study was conducted retrospectively at Patan Hospital from July 2022 to July 2024. Data from 375 patients with ACS were reviewed, including age, sex, comorbidities, and coronary angiogram findings. The data were analyzed using descriptive statistics. Results: The mean age of patients was 60.81 ± 10.75 years, with 54.13% being male. Hypertension (30.67%) and diabetes (21.07%) were the most prevalent comorbidities. Coronary angiograms revealed normal arteries in 51.20% of patients, while 22.93%, 12%, and 9.97% had single-vessel disease (SVD), double-vessel disease (DVD), and triple-vessel disease (TVD), respectively. Management strategies included medical management for 57.87% of patients, while 39.47% underwent percutaneous coronary intervention (PCI). Conclusion: The majority of the subjects with acute coronary syndrome were middle-aged males. The burden of ACS was exacerbated by prevalent risk factors such as hypertension, diabetes, and smoking. Timely diagnosis and management of ACS, including early initiation of medical management and appropriate use of interventions like percutaneous coronary intervention (PCI).